English literature - Nguyễn Chí Trung (Quảng Nam : Giáo dục, 2000)
The Renaisance; The Classic literature; The Age of Englishtment; The XIXth-Century English literature; English literature Critical Realism.
Keywords: English language; Literature; English literature